Improving nutrition outcomes through enhanced allocative efficiency of investments in 24 high risk counties in Kenya: An Optima Nutrition modelling study - Morris Ogero; Nick Scott; Veronica Kirogo; Anthony K. Ngugi (PLoS ONE, 2025)
Introduction Undernutrition remains a significant global challenge, severely impacting children’s development and growth. To address this, the Sustainable Development Goals target a substantial reduction in stunting and wasting by 2025. Achieving these goals requires scaling up evidence-based nutritional interventions; however, limited budgets pose challenges in funding all necessary programs. To assist policymakers in making informed decisions, the World Bank developed the Optima Nutrition Modelling tool, which optimizes the allocation of nutrition investments. Kenya, with its high prevalence of stunting, was the focus of this study. Using the Optima Nutrition model, we aimed to (1) assess the impact of scaling up evidence-based nutrition interventions and (2) determine how existing resources could be optimized to reduce stunting, wasting, and anemia in children under five and anemia in pregnant women across 24 counties with the poorest nutrition outcomes. Methods Utilizing the Optima Nutrition model, we analyzed demographic and intervention data to assess the impact and allocation of interventions. Scenario analyses and optimization techniques were employed to reallocate resources and evaluate their potential impact on reducing undernutrition. Results When scaled up to 95% coverage and maintained until 2030, across the counties the interventions resulted in median relative reductions of 14.6% in stunting prevalence, 23% in wasting prevalence, 20.6% in anaemia prevalence among children and 64.2% in anaemia prevalence among pregnant women. For stunting, the optimized scenarios prioritized infant and young child feeding education, vitamin A supplementation, lipid-based nutrition supplements for children, and balanced energy-protein supplementation and multiple micronutrient supplementation for pregnant women. For wasting, cash transfers was prioritized. For anaemia in children, long-lasting insecticide treated bednets and IFA fortification of maize were prioritized. For anaemia in pregnant women, multiple micronutrient supplementation, iron and folic acid supplementation and long-lasting insecticide-treated bed nets were prioritized. Conclusion This study provided a comprehensive assessment of the prevalence of stunting, wasting, and anemia among children under five years in 24 counties in Kenya. The Optima model suggested that scaling up nutrition-specific interventions under the same baseline budgets could lead to significant reductions in stunting, wasting, and anemia in Kenya. Additionally, the study identified interventions that should be prioritized during nutrition intervention resource allocation.